2016
DOI: 10.1186/s12889-016-3172-0
|View full text |Cite
|
Sign up to set email alerts
|

Accelerometry and physical activity questionnaires - a systematic review

Abstract: BackgroundThe aim of this study is to review accelerometer wear methods and correlations between accelerometry and physical activity questionnaire data, depending on participant characteristics.MethodsWe included 57 articles about physical activity measurement by accelerometry and questionnaires. Criteria were to have at least 100 participants of at least 18 years of age with manuscripts available in English. Accelerometer wear methods were compared. Spearman and Pearson correlation coefficients between questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
248
0
20

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 307 publications
(307 citation statements)
references
References 88 publications
17
248
0
20
Order By: Relevance
“…A recent study from Switzerland reported that time spent physically active was 4.2 times higher according to self‐reported questionnaires than measured with accelerometers . Several other studies also showed substantial differences between self‐reported physical activity and objective measurements . The available RR estimates are also based on self‐reported activity levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study from Switzerland reported that time spent physically active was 4.2 times higher according to self‐reported questionnaires than measured with accelerometers . Several other studies also showed substantial differences between self‐reported physical activity and objective measurements . The available RR estimates are also based on self‐reported activity levels.…”
Section: Discussionmentioning
confidence: 99%
“…36 Several other studies also showed substantial differences between selfreported physical activity and objective measurements. 37 The available RR estimates are also based on self-reported activity levels. Assuming a decreasing risk of disease for increasing physical activity, we would expect higher RR based on accelerometer measurements than based on selfreporting.…”
Section: Discussionmentioning
confidence: 99%
“…This is because accelerometry provides the ability to objectively measure acceleration, from which PA can be estimated, in the same timeframe as traditional observation methods, with the addition of more detail of intensity than subjective PA recall diaries and self-report methods. 8 However, the use of accelerometry at pre-school age is currently limited by the lack of evidence indicating the validity of current accelerometer models and established cut points for determining PA intensity. There is considerable variation in the values of cut points provided for the same placement (eg, hip vs wrist) and epoch lengths for pre-schoolers.…”
Section: Dobell Et Almentioning
confidence: 99%
“…On the other hand, questionnaires capture different aspects of SB because they provide information on the context . For future studies, a combined use of questionnaires and accelerometers is recommended in order to receive the most comprehensive SB information . Keeping in mind that SB includes multiple domains, dimensions, and correlates, there remain many methodological challenges of measuring SB …”
Section: Perspectivesmentioning
confidence: 99%